2016
DOI: 10.1111/dmcn.13238
|View full text |Cite
|
Sign up to set email alerts
|

Complexity as a continuum of many health‐related challenges

Abstract: This commentary is on the review by Glader et al. on pages 1116–1123 of this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Findings from these studies support the idea that caregiver health is associated with the complexity of the caregiving role [15]. Caregiving complexity for parents of children with chronic illness may be viewed as a multi-faceted concept that incorporates the impact of the clinical or medical severity of the child’s disease as well as the social, time, and economic implications of caregiving, which may vary according to child, parent, family, and environmental circumstances [22].…”
Section: Introductionmentioning
confidence: 70%
“…Findings from these studies support the idea that caregiver health is associated with the complexity of the caregiving role [15]. Caregiving complexity for parents of children with chronic illness may be viewed as a multi-faceted concept that incorporates the impact of the clinical or medical severity of the child’s disease as well as the social, time, and economic implications of caregiving, which may vary according to child, parent, family, and environmental circumstances [22].…”
Section: Introductionmentioning
confidence: 70%
“…Caring for children with CCN is challenging, as each child needs an individualized and dynamic plan involving a range of care providers (Brenner et al, 2018). Previous studies have demonstrated that caregivers of children with CCN experience distress and emotional burden as a result of inadequate support from professionals (Brehaut & Kohen, 2016;Brenner et al, 2018;Carter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%